Extra alliteration on stressed syllables in Old English poetry: types, uses and evolution - Griffith, M (Cambridge University Press, 2020)
The article assesses the rhetorical uses of the main kinds of non-functional alliteration that are attested in Old English poetry, and gives complete lists of their incidence in all of the poems. Two main general types are isolated. Supererogatory alliteration does not depart from the known alliterative rules, and is deployed ornamentally with some freedom by at least some of the poets. Five sub-types are examined in turn: double alliteration in the a-verse, consonant cluster alliteration, alliteration which is continued across lines, patterned alternation of alliteration across lines, and enjambed alliteration (where the last stress of a line initiates the alliteration of the next). Secondly, licentious alliteration draws a line‘s final stress into alliteration in its own line. Four sub-types are considered: crossed, postponed, and transverse alliteration, and double alliteration in the b-verse. Whilst crossed alliteration appears quite freely, the primary alliteration of a line on the final stress is shown to be avoided almost completely. Most of the unusual uses of extra alliteration congregate in non-traditional or late poetry.